2021
DOI: 10.1016/j.ppedcard.2021.101407
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated Multisystem Inflammatory Syndrome in Children (MIS-C) guidelines; revisiting the Western New York approach as the pandemic evolves

Abstract: Multisystem inflammatory syndrome of children (MIS-C) continues to be a highly concerning diagnosis in those recently infected with SARS-CoV-2. The diagnosis of MIS-C cases will likely become even more challenging as vaccine uptake and natural immunity in previously infected persons leads to lower circulating rates of SARS-CoV-2 infection and will make cases sporadic. Febrile children presenting with cardiac dysfunction, symptoms overlapping Kawasaki disease or significant gastrointestinal complaints warrant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 82 publications
(111 reference statements)
0
17
0
1
Order By: Relevance
“…Considering the polyclonal antibody response of natural infection against spike surface proteins (including receptor binding domain proteins) and nucleocapsid proteins, the use of serological test specific for spike proteins or nucleocapsid protein can help distinguish between a previous exposure to infection or to a vaccine-spike-protein based response. The determination of antibody against nucleocapsid protein is also part of differential diagnosis of MIS-C [ 55 57 ].…”
Section: Diagnosis Of Sars-cov-2/covid-19mentioning
confidence: 99%
“…Considering the polyclonal antibody response of natural infection against spike surface proteins (including receptor binding domain proteins) and nucleocapsid proteins, the use of serological test specific for spike proteins or nucleocapsid protein can help distinguish between a previous exposure to infection or to a vaccine-spike-protein based response. The determination of antibody against nucleocapsid protein is also part of differential diagnosis of MIS-C [ 55 57 ].…”
Section: Diagnosis Of Sars-cov-2/covid-19mentioning
confidence: 99%
“…1 ) . All were treated with IVIG, methylprednisolone and anakinra, received aspirin, and completed steroid tapers following our published protocol [1] . All of the cases of MIS-C in this study met the MIS-C CDC definition and were reported to the New York State Public Health Department.…”
Section: Resultsmentioning
confidence: 99%
“…Multisystem Inflammatory Syndrome in Children (MIS-C), is marked by high inflammatory markers, organ dysfunction, and symptomatic overlap with inflammatory conditions such as Kawasaki disease [1] . Early in the pandemic it was unclear if vaccination should be encouraged for those who recovered from MIS-C.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of MIS-C cases will likely become even more challenging after vaccine uptake or natural acquired immunity [ 110 , 112 ]. It is unclear why the disease progresses to severe MIS-C in some children, although they have anti-SARS-CoV-2 antibodies.…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)mentioning
confidence: 99%